The “prostate-pelvic syndrome” theory used in patients with type-III prostatitis and its correlation with prostate volume - Xiao-Ma Zhang; Wei-Yi Li; Zong-Yao Hao; Lei Zhou; Cheng Yang; He-Xi Du; Chao-Zhao Liang (BMC Urology)
Abstract Background Type-III prostatitis is the most common prostate disease in adult males below 40 years old. The actual operation of its diagnosis process is cumbersome. Recently, a group of top Chinese urologists have proposed the theory of “prostate-pelvic syndrome (PPS)” and suggested using it to replace the traditional term for type-III prostatitis. However, the practical application effectiveness of PPS theory in clinical practice is still unclear. Objective The aims of this study were to verify the clinical outcome of PPS theory in diagnosing the adult patients with type-III prostatitis below 40 years old and analyze the related factors for the main symptoms of PPS in adult males below 40 years old, providing references for the prevention and treatment of PPS in young adult males. Methods The clinical medical records of 548 adult outpatients with type-III prostatitis under 40 years old between August 2018 and May 2023 were retrospectively analyzed. The patients were diagnosed retrospectively again by using PPS diagnostic criteria in this retrospective cohort study. Subsequently, the age, disease duration, prostate volume (PV), PV ≥ 20 mL detection rate and other related indicators among different symptom groups were analyzed by univariate analysis. The correlation between different symptoms of PPS patients and PV as well as disease duration was analyzed by correlation analysis. Additionally, the related factors for different main symptoms of PPS patients were analyzed by multivariate analysis. Results Of the 548 patients, 229 patients had lower urinary tract symptoms, 159 patients had pelvic pain symptoms, and 160 patients had lower urinary tract and pelvic pain symptoms, respectively corresponding to those with voiding symptoms (VS), pain symptoms (PS), and voiding + pain symptoms (VS + PS) defined according to the concept of PPS. There were significant differences in PV and disease duration among the three main symptoms groups of PPS. PV in the VS group was larger than that in the PS group. Spearman correlation analysis showed that VS was positively correlated with PV and disease duration, while four secondary symptoms (including sexual dysfunction, psychosocial symptoms, reproductive dysfunction and other symptoms) were not related to PV. The proportion of VS patients in the PV ≥ 20 mL group was higher than that in the PV < 20 mL group. Multivariate logistic analysis showed that PV and disease duration were independent related factors for VS in adult PPS patients below 40 years old. Conclusions Type-III prostatitis in Chinese adult males below 40 years old can be diagnosed and treated with PPS. PV and disease duration were independent related factors for VS in Chinese adult PPS patients below 40 years old. The risk of VS in PPS patients with PV ≥ 20 mL was 5.348 times as long as that in PPS patients with PV < 20 mL.